The Nazis' Last Victims : the Holocaust in Hungary. - Braham, Randolph L.; Miller, Scott, 1958- (Wayne State University Press, 2002)
The Nazis' Last Victims articulates and historically scrutinizes both the uniqueness and the universality of the Holocaust in Hungary, a topic often minimalized in general works on the Holocaust. The result of the 1994 conference at the United States Holocaust Memorial Museum on the fiftieth anniversary of the deportation of Hungarian Jewry, this anthology examines the effects on Hungary as the last country to be invaded by the Germans.